Strategies for Mitigating Runout Interference in Torsional Vibration Measurement of Diesel Engine Crankshafts - Chenghao Qi; Zhongxu Tian (Applied Sciences)
The precise measurement of crankshaft torsional vibration is critical for diesel engine reliability, yet it is often compromised by systematic errors from toothed disc runout. To address this challenge, this paper elucidates the dual mechanism of these errors, which manifest as micro-level voltage fluctuations in signal and macro-level time-domain deviations. Based on this understanding, a composite compensation method is proposed. First, a dual-line approximation method is presented for preprocessing the raw sensor signals, aiming to eliminate the distortion in rotational speed calculations caused by anomalous voltages. Second, a synchronous sampling scheme based on the differential measurement principle is developed. This scheme utilizes a symmetrically arranged dual-sensor structure to suppress runout errors and is combined with a time-domain feature reconstruction technique to restore the true rotational speed signal. Validation on a custom-built universal joint torsional vibration test rig demonstrates that the proposed method can effectively eliminate systematic deviations arising from toothed disc runout, thereby significantly enhancing the accuracy of torsional vibration measurements. The measurement method presented in this paper offers a valuable reference for the high-precision measurement of engine torsional vibration characteristics.